[tex]\dfrac{36^6}{27^5\cdot8^5}=\dfrac{(6^2)^6}{(3^3)^5\cdot(2^3)^5}=\dfrac{6^1^2}{3^1^5\cdot2^1^5}=\dfrac{3^1^2\cdot2^1^2}{3^1^5\cdot2^1^5}=\dfrac{3^1^2}{3^1^5}\cdot\dfrac{2^1^2}{3^1^5}=3^{12-15}\cdot2^{12-15}=\\\\\\=3^{-3}\cdot2^{-3}=(\frac{1}{3})^3\cdot(\frac{1}{2})^3=(\frac{1}{3}\cdot\frac{1}{2})^3=(\frac{1}{6})&^3=\frac{1}{216}[/tex]
[tex]Zastosowane\ \ wzory\\\\(a^m)^n=a^{m\cdot n}\\\\\frac{a^m}{a^n}=a^{m-n}\\\\a^{-n}=(\frac{1}{a})^n\ \ \ \ dla\ \ a\neq 0\ \ (mianownik\ \ nie\ \ mo\.ze\ \ by\'c\ \ zerem)[/tex]